Impact of Overweight on Spatial–Temporal Gait Parameters During Obstacle Crossing in Young Adults: A Cross-Sectional Study - Chardon, Matthias [UNESP]; Barbieri, Fabio Augusto [UNESP]; Hansen, Clint; Petit, Pascal; Vuillerme, Nicolas (MDPI, 2024)
Background: Overweight may present an additional challenge when crossing obstacles. More specifically it may affect adequate foot clearance to reduce the risk of obstacle contact. Thus, the objective of this study was to compare obstacle clearance and spatial–temporal gait parameters during obstacle crossing in young adults with normal body weight and overweight. Methods: Twenty-eight and fifteen individuals were categorized into normal body mass index (18.5–25 kg/m2) and overweight (25–30 kg/m2), respectively. The participants walked along a walkway at their preferred speed and stepped over an obstacle. Spatial–temporal parameters were calculated during the approaching (stride before obstacle) and the crossing (step over the obstacle) phases. Additionally, the leading and trailing foot placements prior to and after the obstacle and toe clearance were calculated. Results: No significant differences were found for the approach, the crossing phases and leading and trailing toe clearance. Analysis of foot placement distance prior to and after the obstacle showed that, compared to the individuals with normal body weight, overweight individuals significantly increased the leading foot placement distance prior to the obstacle (+7 cm, ↑ 6.7%) and increased the trailing foot placement distance after the obstacle (+8.1 cm, ↑ 9%). Conclusions: Our findings indicated that overweight individuals have a different obstacle crossing behavior regarding foot placement distance prior to and after the obstacle compared to normal-weight individuals without differences in spatial–temporal gait parameters or toe clearances. However, the results did not suggest that participants with overweight show a higher risk of tripping.
Keywords: clearance; gait; obstacle crossing; overweight